Variação nas características físicas de morangas e abóboras durante o armazenamento - Fernandes Pedrosa, Josué; Dias Casali , Vicente Wagner; de Carvalho, Vânia Déa; Fernandes Chitarra, Maria Isabel (Revista Ceres, 2025)
Changes in physical characteristics of squash (Cucurbita mazima Duch) and pumpkin (Cucurbita moschata Duch) were determined at 14 day intervals over a 70-day storage period.